Rare bird documentation form for Pine Grosbeak at State Center, 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Rare bird documentation form for a Pine Grosbeak at State Center in Marshall County, IA on March 8, 1981. Epson - sheet feed